ORGANIZATIONAL CLIMATE ANALYSIS AND PERFORMANCE ON JOB SATISFACTION OF MEDICAL AND MEDICAL PERSONNEL AT THE REGIONAL GENERAL HOSPITAL OF CIAMIS DISTRICT - Bustomi, Thomas; Satibi, Iwan; ., Rustandi (Department of Government, FISIP, Universitas Padjadjaran, 2021)
This study aims to examine how the influence of organizational climate and performance on the job satisfaction of medical workers and medics at the Ciamis District General Hospital. The research uses quantitative research methods and refers to the theory of organizational climate and performance, which has six aspects: structure, standards, responsibility, rewards, support, commitment, and other items ranging from work accuracy, job reviews, etc. The population of this study were employees at the Tasikmalaya and Banjar City General Hospitals. A sample of 98 respondents was taken using proportional random sampling. They were collecting data using a questionnaire designed by the needs of research and observation. The results of this study indicate that the organizational climate and performance have a significant influence on the job satisfaction of medical workers and medics at the Ciamis District General Hospital. On the other hand, the dimensions of the structure, the dimensions of standards and the dimensions of commitment have no significant effect on the job satisfaction of medical workers and medics at the Ciamis District General Hospital. The organizational climate, especially human resources, is still limited at the Ciamis District General Hospital, showing the strength displayed by medical personnel and medical staff, where medical personnel can display ways and strategies in building structure, responsibility, support, commitment with all their subordinates, especially helping provide more effective care for all patients.gb777